Dietary glycemic index, glycemic load, insulin index, fiber and whole grain intake, in relation to risk of prostate cancer - Nimptsch, K (2010)
OBJECTIVE: Insulin may play a role in prostate cancer tumorigenesis. Postprandial blood glucose and insulin responses of foods depend importantly on the carbohydrate quality and quantity, represented by glycemic index (GI), glycemic load (GL), fiber, and whole grain content, but are also influenced by intake of protein and other characteristics. The recently developed insulin index (II) quantifies the postprandial insulin secretion, also taking into account these additional characteristics. METHODS: We investigated the association between dietary GI, GL, II, fiber and whole grains and risk of total prostate cancer (n=5,112) and subgroups of prostate cancer as defined by stage or grade in 49,934 male participants of the Health Professionals Follow-up Study. Multivariate adjusted hazard ratios (HR) and 95% confidence intervals (95% CI) were estimated using Cox proportional hazards regression. RESULTS: Dietary GI, GL, II or fiber were not associated with risk of total or subgroups of prostate cancer. We observed a positive association between dietary intake of whole grains and total prostate cancer (HR highest versus lowest quintile 1.13, 95% CI 1.03–1.24), which was attenuated after restriction to PSA-screened participants (HR 1.03, 95% CI 0.91–1.17). CONCLUSIONS: These results suggest that long-term exposure to a diet with a high insulin response does not affect prostate cancer incidence.